Ambient Intelligence 4th International Joint Conference, AmI 2013, Dublin, Ireland, December 3-5, 2013. Proceedings - Augusto, Juan Carlos; Wichert, Reiner; Collier, Rem; Keyson, David; Salah, Albert A.; Tan, Ah-Hwee (Information Systems and Applications, incl. Internet/Web, and HCI, 2013)
This book constitutes the refereed proceedings of the 4th International Joint Conference an Ambient Intelligence, AmI 2013, held in Dublin, Ireland, in December 2013. The 15 revised full papers, 4 papers from the landscape track, 3 papers from the doctoral colloquium, and 6 demo and poster papers were carefully reviewed and selected from numerous submissions, and are presented with 6 workshop descriptions. The papers cover a variety of multi-disciplinary topics in computer science, human computer interaction, electrical engineering, industrial design, behavioral sciences, distributed devices, ubiquitous and communication technologies, pervasive computing, intelligent user interfaces and artificial intelligence.